2009
DOI: 10.2353/ajpath.2009.090152
|View full text |Cite
|
Sign up to set email alerts
|

The Stent-Eluting Drugs Sirolimus and Paclitaxel Suppress Healing of the Endothelium by Induction of Autophagy

Abstract: Clinical studies have indicated that the stent-eluting drugs sirolimus and paclitaxel impact restenosis; however, it is still elusive how these drugs affect the vascular endothelium at the molecular and cellular levels. The purpose of this study was to determine whether sirolimus and paclitaxel induce molecular and cellular alterations in the vascular endothelium. Endothelial regrowth was assessed in human aortic endothelial cells and rat aortic endothelium. Molecular and cellular alterations were analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…For example, autophagy activation can protect ischemic cell injury [40], extend lifespan in mice [41] and promoting EPC angiogenesis in cancer development [42,43]. Recently, more evidences have suggested that acute increase in autophagy is protective under hypoxia and chronic ischemia conditions, whereas chronic increase in autophagy may lead to apoptosis [44][45][46][47]. Thus, to demonstrate the therapeutic effect of autophagy in DVT, future studies are needed to investigate autophagy kinetics in DVT and its role in thrombus recanalization in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…For example, autophagy activation can protect ischemic cell injury [40], extend lifespan in mice [41] and promoting EPC angiogenesis in cancer development [42,43]. Recently, more evidences have suggested that acute increase in autophagy is protective under hypoxia and chronic ischemia conditions, whereas chronic increase in autophagy may lead to apoptosis [44][45][46][47]. Thus, to demonstrate the therapeutic effect of autophagy in DVT, future studies are needed to investigate autophagy kinetics in DVT and its role in thrombus recanalization in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, rapamycin and its analogs are used clinically to limit VSMC proliferation, such as in drug-eluting coronary artery stents (126,127). Sirolimus from drug-eluting stents induces autophagy in vascular endothelial cells suppressing reendothelialization and revascularization (128).…”
Section: Autophagy In Vascular Remodelingmentioning
confidence: 99%
“…Vincent et al (14) described antiproliferative effects of CA4 on endothelial cells at nontoxic doses of 5 nmol/L and 10 nmol/L. Also, Hayashi et al (15) showed inhibitory effects of sirolimus and paclitaxel on the cell cycle in the low nanomolar range. To ensure comparability, we chose 5 Â 10 À9 mol/L as the concentration in all experiments.…”
Section: Treatment Of Human Aortic Smcsmentioning
confidence: 96%